The Syntactical Analysis Of Sentence Patterns Of Make Over Lipstick Advertisement Found In Instagram Applied In Tree Diagram - Budianto, Suhartawan; Amaliyah, Rochmathul (Faculty of Letters, Dr. Soetomo University, 2017)
The science of language is known linguistics. Syntax is a branch of linguistics that studies the set of words, phrases, clauses in a sentence. The researcher focuses her research on sentence pattern in Make Over lipstick advertisement found in instagram. The objective of this research are to analyze the syntactical structure of sentence pattern applied in tree diagram and transformation grammar. The tree diagram used to describe words, phrases, or clauses arranged in a sentence. While the transformation grammar function to find out the changes in the shape of a sentence. In analyzing the data in tree diagram the researcher uses Dianne Borstein theory and for analyzing the data in transformation grammar uses Akmajian and Frank theory. The researcher uses descriptive qualitative methods to describe and explain the finding data. The data found were thirteen data taken through the selection of sentences based on their types, namely declarative sentence, question sentences, and exclamation sentences. The data is then analyzed. From the analysis carried out, the reseracher found declarative sentences and exclamation sentences on the basic structure of sentences while the command sentences and question sentences are in the transformation grammar structure. Key Words : Syntactical Analysis, sentence pattern, Instagram advertisement.